(untitled) (Psychology Travelogs, 2022)
Speech is evidence of a person’s language culture, his mental and personal development. The attention of researchers is due to the need to solve one of the key tasks of preschool education - the formation of the speech personality of a preschooler. The content of speech personality formation in preschool age is determined by children’s speech development programs and normative documents for preschool. The relevance of timely speech development in preschool childhood is determined by the tasks of creating optimal conditions for the fullest possible disclosure of the potential capabilities of each child, which are manifested in specifically children’s activities and are related to communication. The formation of all mental functions, mental processes, personality in a person as a whole is impossible without interpersonal contact. At the same time, speech development and its improvement must be considered as a reflection of the formation of communication and speech interaction skills. The ability to communicate is understood as a comprehensive ability to use means of interaction that ensure the success of communication goals. Unfortunately, in the speech development of preschool children, problematic situations often arise that become a threat to the child’s further speech activity. This is later reflected in her emotional and psychological state, manifests itself in the educational process, so I can correct the situation by contacting a specialist in time. Adults should know and understand directions for the development of speech activity in preschool age and make efforts to optimize it, especially during the organized education of children in preschool education institutions. Prospects for further research are the study of the influence of gadgets on the speech activity of preschoolers and the position and role of adults in this regard.